Bench shoes storage / Luqman Hakim Mohd Agus Adib - Mohd Agus Adib, Luqman Hakim (2019)
In this study, Blockboard has been used as the raw material in this product manufacturing. It has good dimensional stability and better ability to hold nails and screws, compared to other engineered wood such as particle boards or MDF (medium density fibreboard). This study objective was conducted to produce Bench Shoes Storage that save space, easy to handle and evaluate customer feedback on quality of Bench Shoes Storage. The data was analysed based on the questionnaire that had been distributed to 150 respondent of different age, gender, profession and income. The characteristics evaluated by respondents include knowledge, design, marketing and satisfaction. Based on customer feedback, the highest feedback is from design factor followed with satisfaction, marketing and knowledge. Overall, this Bench Shoes Storage is well accepted by most of the correspondence since it provides benefits to the consumers.